2015
DOI: 10.4238/2015.may.25.11
|View full text |Cite
|
Sign up to set email alerts
|

FSHR gene Thr307Ala and Asn680Ser polymorphisms in infertile men: an association study in North China and meta-analysis

Abstract: ABSTRACT. Male infertility is a complex multifactorial and polygenic disease, and genetic factors play an important role in its formation and development. Recently, the association between follicle stimulating hormone receptor (FSHR) gene polymorphisms and male infertility risk has attracted widespread attention due to the unique biological functions of FSH. The aim of this study was to further explore the associations between the Thr307Ala and Asn680Ser polymorphisms of the FSHR gene and male infertility. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…To resolve the conflicting results, we carried out a meta-analysis to obtain a more precise estimation of the associations. Contrary to previous meta-analyses that found no significant association between FSHR rs1394205 (G-29A), rs6165 (Thr307Ala), or rs6166 (Asn680Ser) polymorphisms and the risk of male infertility [ 2 , 30 , 34 ], this study indicated that the rs6165G allele was associated with increased risk of male infertility, particularly in the subgroup analysis of HWE > 0.05. In addition the rs6166 GG genotype was also observed to be a risk factor for infertility in the subgroup analysis of HWE > 0.05.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To resolve the conflicting results, we carried out a meta-analysis to obtain a more precise estimation of the associations. Contrary to previous meta-analyses that found no significant association between FSHR rs1394205 (G-29A), rs6165 (Thr307Ala), or rs6166 (Asn680Ser) polymorphisms and the risk of male infertility [ 2 , 30 , 34 ], this study indicated that the rs6165G allele was associated with increased risk of male infertility, particularly in the subgroup analysis of HWE > 0.05. In addition the rs6166 GG genotype was also observed to be a risk factor for infertility in the subgroup analysis of HWE > 0.05.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 15 studies, 4 studies from Asian population [ 24 , 28 30 ] and 11 studies from non-Asian population [ 1 , 13 , 14 , 16 , 17 , 22 , 31 35 ], met the inclusion criteria (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reports suggest no significant differences in carrier frequencies of individual FSHR Asn680Ser polymorphic variants between infertile and fertile men from various ethnic groups 6,8,9,[27][28][29][30][31][32][33][34][35][36] . The same results were obtained in a meta-analysis of these studies [8][9][10][11] . Similarly, the effect of Asn680Ser FSHR isoforms on clinical reproductive parameters such as FSH level, sperm count and total testis volume also failed to show any consistent associations 16,[28][29][30]33,34,37,38 .…”
Section: Discussionsupporting
confidence: 81%
“…For example, Wu et al report that homozygous combination of FSHR gene polymorphism at codon 307 and 680 (i.e. Thr/Thr + Asn/Asn) may be responsible for male infertility in patients from north China 11 . In addition, Lindgren et al report that Thr307-Asn680 homozygotes in a Swedish cohort of young men among others exhibited lower serum FSH and higher total testosterone concentrations, as well as larger testis volume and higher sperm count when compared with heterozygotes and Ala307-Ser680 homozygote carriers 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation